Implementasi pendidikan inklusif bagi anak berkebutuhan khusus di madrasah - Hasanah, Nur; Asdiqoh, Siti; Famularsih, Sari (Nur Science Institute, 2024)
Inclusive education is an educational service system that ensures all children with special needs (ABK) have access to education at their nearest school or madrasah and learn alongside other students in regular classrooms. The presence of inclusive education makes a significant contribution to achieving educational equity for all children, regardless of their diverse abilities and characteristics. This study aims to investigate the implementation of inclusive education for children with special needs at MAN 2 Klaten. The research method employed is qualitative, utilising data collection techniques that include observation, interviews, and documentation. The research approach is qualitative, employing a descriptive, exploratory, and analytical method. The results of the study indicate that the implementation of inclusive education at MAN 2 Klaten is carried out through three stages, namely: (1) planning, which includes preparation of teaching and learning activities, development of teacher work plans, internal coordination, and scheduling of learning; (2) implementation, which uses lecture and question-and-answer methods supported by auxiliary media such as books and Braille; and (3) evaluation, which is conducted orally by reading questions to students until they are understood, and in writing using Braille questions.